Investigating the impact of human-centric public transport design principles on the desirability and operational success of public transport in the Western Cape Province, South Africa -- a mixed-methods study - Carstens, Rain (Stellenbosch : Stellenbosch University, 2022)
Thesis (MEng)--Stellenbosch University, 2022.